PENGARUH LABELISASI HALAL DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MUSLIM PADA PRODUK KOSMETIK - Siti Rohamah; Moh. Bahruddin; Heni Noviarita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effect of halal labeling and brand image on purchasingdecisions. The research method in this research is using quantitative research methods. Thepopulation in this study are consumers who buy Wardah cosmetic products in Bandar LampungCity. The sampling technique in this study used a purposive sampling method with a sample of100 respondents. The data analysis technique used is multiple linear regression analysis. Thetest results show that halal labeling and brand image have a significant effect on purchasingdecisions. Based on the results of the calculation of the coefficient of determination (R2)obtained a value of 0.772. this can explain that the variable labeling halal and brand image isable to explain the variable purchasing decisions by 77.2%. So it can be said that 77.2% of thepurchasing decision variables can be explained by a temporary model and the remaining22.8% is influenced by other factors not included in this study.